Pengaruh Iklan Produk Di Aplikasi, Promosi Penjualan, Brand Ambassador Shopee, Dan Kualitas Layanan Terhadap Minat Beli Di Marketplace Shopee - Ayu Yulianti Putri (Manajemen Kreatif Jurnal, 2023)
After the covid pandemic conditions, new habits and trends in society are slowly starting to change, one of which is the shift from offline to online shopping. Since the pandemic took place, people’s offline purchasing power has decreased. Shops or shopping centers are empty of visitors and most prefer to shop online or online. In Indonesia, there are several marketplaces operating such as Shopee, Tokopedia, Bukalapak, Lazada and Bblibli. Shopee Indonesia is the Marketplace with the most visitors in the 4th quarter of 2022. With an average of 191.60 million visitors. So, currently Shopee is the most popular and visited Marketplace. As a company, Shopee uses various marketing channels to increase consumer buying interest. In this study, researchers analyzed the influence of advertising in the Shopee application, sales promotions, brand ambassadors, and service quality on consumer buying interest in the Shopee application. This quantitative study took data from 384 Shopee users who were analyzed using measurement model evaluation analysis which included validity and reliability tests, and structural model testing which included the Goodness of Fit Model and hypothesis testing. In the first stage of analysis, all variables are declared valid and reliable. Then in the second analysis stage, it shows that product advertisements in applications, sales promotions, brand ambassadors and service quality carried out by Shopee have an effect on consumer buying interest to shop on the Shopee application.